Two new species of the sac-spider genus Clubiona Latreille, 1804 (Araneae, Clubionidae) and the female of C. subcylindrata from China - Li, Li-Fen; Liu, Ping; Li, Bing; Peng, Xian-Jin (Zootaxa, 2023)
Two new species of the genus Clubiona Latreille, 1804 are described: C. tianpingshan sp. nov. (♂♀) and C. flammaforma sp. nov. (♂♀) from central and south China. The female of C. subcylindrata Wang et al., 2018 is described for the first time. Detailed descriptions, photographs of somatic features and copulatory organs, as well as a distribution map of these three species, are provided.